“It Is a Very Emotional Topic for Me”—Managing Breastfeeding Problems among German Mothers: A Qualitative Approach - Spannhake, Mariz; Jansen, Charlotte; Goerig, Tatiana; Diehl, Katharina (Healthcare, 2021)
Breastfeeding is associated with positive health outcomes for both child and mother. Nev-ertheless, some women experience breastfeeding problems which commonly lead to early cessation, or not starting breastfeeding at all. Our aim was to explore how women that have difficulties in breastfeeding perceive their situation and how they actively manage it. We conducted semi-struc-tured interviews with 15 mothers living in Germany who had experienced breastfeeding problems. The interviews were audio-recorded, transcribed verbatim, and analyzed using qualitative content analysis. Breastfeeding problems occurred due to different reasons and had a huge impact, as evi-denced in the four main themes of the findings: individual situation, managing the situation, perceived consequences for relations, feelings, and potential future pregnancies, and perceived health consequences for the mother. They frequently experienced negative emotions, including psychological distress and mental health problems, with perceived negative consequences for the mother– infant-bonding. Trying to actively manage the situation and availability of social support seemed to have a relieving effect, whereas confrontation and lack of understanding worsened the situation. Breastfeeding problems and the inability to breastfeed can have a great influence on maternal well-being. These can affect different aspects of a mother’s life, including the attachment to the child. Providing support for actively managing the situation and supporting the exchange of experience between mothers who perceive breastfeeding problems may help mothers to better deal with their situation. Our findings may help health professionals to understand what these mothers feel and how they can support these women in a sensitive way.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Breast pump; Breastfeeding; Children; Difficulties in breastfeeding; Germany; Mothers; Qualitative study; Stress